Conflicts of Interest in Financial Intermediation - Palazzo, Guido (Journal of business ethics, 2008)
The last years have seen a surge of scandals in financial intermediation. This article argues that the agency structure inherent to most forms of financial intermediation gives rise to conflicts of interest. Though this does not excuse scandalous behavior it points out market imperfections. There are four types of conflicts of interest: personal-individual, personal-organizational, impersonal-individual, and finally, impersonal-organizational conflicts. Analyzing recent scandals we find that all four types of conflicts of interest prevail in financial intermediation.